Estrus pattern and conception rate in postpartum lactating Ongole (Zebu) cows - NAIDU, G VENKATA; RAO, K BABU (The Indian Journal of Animal Reproduction, 2023)
A total of 131 parous lactating cows were observed for postpartum ovarian activity and other estrual events from day 15 postpartum. Observable estrus was noticed in 64.12 and 35.89 per cent of cows before day 60 ( 16 - 60) and beyond day 60 (61 -165), respectively. The mean time interval from calving to first postpartum onset of estrus was found to be 59. 76 ± 2.8 I days. The incidence of estrus was observed to be more (61.83%) during night (6 PM to. 6 AM). The other estrual events viz. estrus duration and estrous cycle length were 15.54 ± 0.28 hr and 22.67 ± 0.56 days, respectively. The conception rate at first Al was 42.74% with an overall fertility of90%. The time interval from calving to conception (SP) and number of Al’s required per conception were 113.52 ± 5.62 (21 - 346) days and 2.42 ±0.11 ( 1-6), respectively.